THE FORMATION OF STRUCTURAL LINGUISTICS AND THEORETICAL FOUNDATIONS OF THE LANGUAGE-SPEECH RELATIONSHIP (Universal International Scientific Journal, 2026)
This article analyzes the formation of structural linguistics, its theoretical foundations, and scientific interpretations of the relationship between language and speech. It also highlights the epistemological, ontological, and pragmatic differences between language and speech phenomena. The research substantiates the importance of structural and functional approaches in the development of modern linguistics.
Keywords: structural linguistics, language and speech, functional linguistics, phonology, Prague linguistic school, language system, linguistic structure, nominative theory, functional approach.